PHOTOLUMINESCENCE MECHANISM OF THE RARE EARTH IONS Eu3+ and Sm3+ DOPED INSIDE TiO2 NANOPARTICLES - Trùng Dương, Nguyễn; Nguyễn, Mạnh Sơn (Hue University Journal of Science: Natural Science, 2019)
The paper studies the luminescence properties of the rare earth ions doped inside TiO2 nanoparticles synthesized using sulfuric acid method. Nanoparticles are investigated by means of X-ray diffraction and transmission electron microscopy. The obtains results of show that there exists a clear difference in the optical mechanism of Eu3+ and Sm3+ doped TiO2 nanoparticles.